2016
DOI: 10.1097/prs.0000000000002551
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ADSC Osteoinductive Potential Using Notch Pathway Inhibition and Gene Rescue: A Potential On/Off Switch for Clinical Applications in Bone Formation and Reconstructive Efforts

Abstract: These data suggest a potential translatable "on/off switch," using endogenous Notch signaling to regulate the proliferation, differentiation, and osteogenic potential of ADSCs. Although Notch inhibition reduced ADSC proliferation and down-regulated osteoinduction, targeted gene therapy and the delivery of the downstream NICD peptide restored bone formation, suggesting pragmatic clinical utility of ADSCs for bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…These findings imply that endogenous Notch signaling may participate in osteogenic differentiation. Previous reports demonstrated that inhibiting endogenous Notch signaling using a γ-secretase inhibitor reduced the osteogenic differentiation of hADSCs and human umbilical cord mesenchymal stem cells as confirmed by a significant reduction in in vitro mineral deposition 34 , 48 . However, osteogenic medium containing DAPT did not alter ALP enzymatic activity or mineralization by hDPs in the present study.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These findings imply that endogenous Notch signaling may participate in osteogenic differentiation. Previous reports demonstrated that inhibiting endogenous Notch signaling using a γ-secretase inhibitor reduced the osteogenic differentiation of hADSCs and human umbilical cord mesenchymal stem cells as confirmed by a significant reduction in in vitro mineral deposition 34 , 48 . However, osteogenic medium containing DAPT did not alter ALP enzymatic activity or mineralization by hDPs in the present study.…”
Section: Discussionmentioning
confidence: 80%
“…However, evidence supporting a positive role in osteogenic differentiation is increasing. Notch signaling promoted osteogenic differentiation in hBMSCs, human periodontal ligament stem cells, human adipose stem cells (hADSCs), and SHEDs 8 , 10 , 12 , 48 51 . The role of Notch signaling in the odonto/osteogenic differentiation of adult dental cells (SHEDs and periodontal ligament stem cells) was previous reported by a few research groups, including our own.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the inhibition of Notch and the associated downregulation of ASC proliferation and osteoinduction has been found to be a useful potential translatable "on/off switch" in the regulation of proliferation, differentiation, and osteogenic potential of ASCs. Additionally, delivery of Notch-1 intracellular domain (NICD), after prior Notch inhibition, restored bone formation [31].…”
Section: Osteogenic Differentiationmentioning
confidence: 99%
“…A recent study reported that Notch signaling is also directly involved in the osteogenic differentiation of ASCs [ 40 ]. It has been shown that Notch pathway activation improves the osteoinductive ability of ASCs and the formation of the extracellular matrix, whereas the Notch inhibition downregulates the osteogenic commitment of these cells [ 40 ]. These studies suggest that the modulation of Notch signaling could be used to stimulate an osteogenic induction of ASCs.…”
Section: Molecular Mechanisms Responsible For Osteogenic Commitmenmentioning
confidence: 99%